(untitled) (The Conference Hub, 2025)
This article discusses the stages of cheese production technology, types of raw materials used, as well as the microbiological and biochemical processes involved. It highlights modern industrial methods, equipment, starter cultures, and differences in preparation techniques depending on cheese types. The article also analyzes advanced approaches to improving product quality, extending shelf life, and preserving nutritional value. It is of practical interest to food industry professionals, technologists, and dairy processing specialists.